Encountering extremism: theoretical issues and local challenges - Martini, Alice; Ford, Kieran; Jackson, Richard (Manchester University Press, 2020)
Introduction: Encountering extremism: a critical examination of theoretical issues and local challenges / Alice Martini, Kieran Ford and Richard Jackson -- What's in a name? Theoretically deconstructing extremism -- Extremism, countering extremism and preventing extremism: from theory to international and local challenges.